Electrochemical kinetics of molten potassium thiocyanate on platinum : Mechanisms of anodic film formation and its cathodic dissolution - Arvia, Alejandro Jorge (1972)
The kinetics and mechanism of the anodic film formation and its cathodic dissolution on platinum, through electrolysis of molten potassium thiocyanate, were studied. Experiments were made at 190°C by applying both repetitive and single pulse linear sweep voltammetry. The kinetics of the anodic film formation is a film-growth-rate controlled process, whose mechanism comprises various steps: discharge, nucleus formation and growth. The discharge step is a fast process and the second step is postulated as rate-determining at low potential sweep rates; the corresponding Tafel slope is RT/2F. At higher potentials the larger reaction rates achieved make reaction sites undistinguishable. This fact reflects a change of reaction mechanism involving a different Tafel slope for the anodic film formation, which is twice the former slope. The corresponding E/I curves are theoretically evaluated with parameters derived from the postulated mechanisms. The dissolution process is not definitely established although the likely pathway is envisaged. The catholic reaction is characterized by a Tafel slope of RT/F. The dissolution comprises a fast electron-transfer step followed by thiocyanate-ion formation; the latter appears as the slowest step.